2008
DOI: 10.3727/096368908786576453
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Cell Transplant does Not Prevent or Reverse Murine Liver Cirrhosis

Abstract: We tested the effect of bone marrow cell (BMC) transplantation in either preventing or reversing cirrhosis on an experimental model of chronic liver disease. Female Wistar rats were fed a liquid alcohol diet and received intraperitoneal injections of carbon tetrachloride (CCl 4 ) over 15 weeks. Ten animals (cell-treated group) received five injections of BMCs during the cirrhosis induction protocol (on the 4th, 6th, 8th, 10th, and 12th weeks) and four animals received the cells after liver injury was establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 51 publications
1
35
0
1
Order By: Relevance
“…Bone marrow blood was aspirated under local anesthesia from both iliac crests and processed to isolate the mononuclear cell fraction. A total of 5ϫ10 8 BMMCs was suspended into a volume of 10 mL, and 1 mL of the cell suspension was radiolabeled with 99m Tc (radioactivity 111 MBq, physical half-life 6 hours), as described previously, 1,2 and then added back to the unlabeled cell suspension. After catheter navigation via femoral artery access under local anesthesia and conscious sedation, cells were injected into the M1 portion of the MCA, and the infusion was completed within Ϸ10 minutes.…”
mentioning
confidence: 99%
“…Bone marrow blood was aspirated under local anesthesia from both iliac crests and processed to isolate the mononuclear cell fraction. A total of 5ϫ10 8 BMMCs was suspended into a volume of 10 mL, and 1 mL of the cell suspension was radiolabeled with 99m Tc (radioactivity 111 MBq, physical half-life 6 hours), as described previously, 1,2 and then added back to the unlabeled cell suspension. After catheter navigation via femoral artery access under local anesthesia and conscious sedation, cells were injected into the M1 portion of the MCA, and the infusion was completed within Ϸ10 minutes.…”
mentioning
confidence: 99%
“…Taken together, the histological and macroscopic features of the liver, mortality rates, and gene expression data support the association of serum parameters with progression of cirrhosis in the present rodent model. Studies carried out in chronic liver disease models have produced controversial results, with positive results in some studies [22] , but not in others [10,23] . These studies tried to establish adequate follow up protocols and some measured serum parameters of liver function, but only at the endpoint.…”
Section: Discussionmentioning
confidence: 99%
“…One of the studies using syngeneic bone marrow MSC in CCl4 induced chronic disease did measure albumin and ALT to assess liver function but also noticed that after a few weeks parameters improved regardless of treatment with MSC [10] . Finally, we chose to evaluate the results one week after treatment as MSC reportedly do not survive longer after injection into immunocompetent animals [23] , and therefore should be able to exert their effect in this narrow timeframe.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the resulting anti-inflammatory effect is less than that seen with MSCs. Experiments using a rat model of severe cirrhosis showed that liver fibrosis was exacerbated by BMNCs transplantation, but was ameliorated by BMSCs transplantation [57] [58] [59]. Similarly, it was demonstrated by the animal experiments that BMSCs had better therapeutic effect on acute liver injury with the respects to anti-inflammation and anti-fibrosis activity [60].…”
Section: Selection Of An Appropriate Stem Cell Typementioning
confidence: 99%